Correlation Between Stunting And Toddler Development - Setianingsih Setianingsih; yulia Lanti Retno Dewi; Sri Mulyani; Ayu Siti Khotidjah (Jurnal Penelitian Perawat Profesional, 2025)
Stunting is still a serious public health problem in Indonesia that has an impact not only on linear growth but also on clind development. Stunting will affect physical performance and mental and cognitive functions will be disrupted. The children are left behind in many areas of child development including; social personality, fine motor, language, and gross motor. This study purposes to determine the relationship between stunting and children’s development. This study used a quantitative method using a cross sectional approach. The study respondents were 190 toddlers obtained by consentive sampling techniques that fit the inclusion and exclusion criteria. The data collection instrument used anthropmetric measurements and the Denver II questionnaire (DDST) is highly sensitive. Analysis of bivariate data using Kendall's Tau test. The results of the study were mostly male stunting toddlers (62.3%), the average age was 31.42 months. The results showed 53 stunting toddlers (100.0%) with normal development of 2 toddlers (3.8%), and suspected or suspected 50 toddlers (96.2%). The results of Kendall's Tau test reveal that there is a relationship between stunting and toddler development with p value =0.000 (p <0.05). Conclusion of stunting has relationship to the development of toddlers in Kemudo Village.